2019
DOI: 10.3390/data4030121
|View full text |Cite
|
Sign up to set email alerts
|

Aspect Extraction from Bangla Reviews Through Stacked Auto-Encoders

Abstract: Interactions between online users are growing more and more in recent years, due to the latest developments of the web. People share online comments, opinions, and reviews about many topics. Aspect extraction is the automatic process of understanding the topic (the aspect) of such comments, which has obtained huge interest from commercial and academic points of view. For instance, reviews available in webshops (like eBay, Amazon, Aliexpress, etc.) can help the customers in purchasing products and automatic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…They claimed the autoencoder had never been used in Bangla for aspect extraction. So these are new things for experiments in Bangla [7]. In [8] the authors found the best accuracy for Bangla Cricket and Restaurant dataset.…”
Section: Related Workmentioning
confidence: 93%
See 1 more Smart Citation
“…They claimed the autoencoder had never been used in Bangla for aspect extraction. So these are new things for experiments in Bangla [7]. In [8] the authors found the best accuracy for Bangla Cricket and Restaurant dataset.…”
Section: Related Workmentioning
confidence: 93%
“…They got 51% and 64% f1-score for the cricket dataset and restaurant dataset respectively. Bodini and Matteo [7] implement three autoencoders for a Bangla Dataset. These are standard AEs, contractive AEs (CAEs), and sparse AEs (SAEs).…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the same year [6] witnessed a study on aspect extraction from financial microblogs, comparing supervised and unsupervised methods for explicit and implicit aspect identification, showing promising results. Additionally, 2019 [7] saw a study introducing classification methods based on stacked auto-encoders for aspect extraction in Bangla reviews, outperforming the state-of-the-art methods.…”
Section: Related Workmentioning
confidence: 99%
“…For the 'Restaurant' dataset, KNN, SVM, and RF classification achieved 42%, 38%, and 38% F1-Score, respectively, while CNN outperformed them with 64% F1-Score. In [16], Boidini implemented three stacked Auto-encoders (AEs) models based on the datasets from [15] to categorize aspects in the Bengali text. The stacking network's layers were individually trained to comprehend the encoded data of the layer that came before them.…”
Section: Literature Reviewmentioning
confidence: 99%